Autolysis‐mediated membrane vesicle formation in Bacillus subtilis. (17th April 2021) - Abe, Kimihiro; Toyofuku, Masanori; Nomura, Nobuhiko; Obana, Nozomu
Summary: It is known that Bacillus subtilis releases membrane vesicles (MVs) during the SOS response, which is associated with cell lysis triggered by the PBSX prophage‐encoded cell‐lytic enzymes XhlAB and XlyA. In this study, we demonstrate that MVs are released under various stress conditions: sucrose fatty acid ester (SFE; surfactant) treatment, cold shock, starvation, and oxygen deficiency. B. subtilis possesses four major host‐encoded cell wall‐lytic enzymes (autolysins; LytC, LytD, LytE, and LytF). Deletions of the autolysin genes abolished autolysis and the consequent MV production under these stress conditions. In contrast, deletions of xhlAB and xlyA had no effect on autolysis‐triggered MV biogenesis, indicating that autolysis is a novel and prophage‐independent pathway for MV production in B. subtilis . Moreover, we found that the cell lysis induced by the surfactant treatment was effectively neutralized by the addition of exogenous purified MVs. This result suggests that the MVs can serve as a decoy for the cellular membrane to protect the living cells in the culture from membrane damage by the surfactant. Our results indicate a positive effect of B. subtilis MVs on cell viability and provide new insight into the biological importance of the autolysis phenomenon in B. subtilis .